Association of nitrosative and oxidative stress in young type 2 diabetic patients - Padhy, Rasmita; Acharya, Suvendu Sekhar; Devi, Nirupama; Swain, S.; Rattan, Roma (International Journal of Research in Medical Sciences, 2017)
Background: Nitric oxide levels play an important role in the pathogenesis of endothelial dysfunction in type 2 diabetes mellitus (DM). Aim of the study was to assess the association between serum nitric oxide levels (NOx), Oxidant load (FOX2) and total antioxidant status (FRAP) with fasting blood sugar (FBS) in type 2 diabetic patients. Methods: Serum concentration NOx was measured by Griess method in seventy six type 2 diabetic patients with age & sex matched (aged 45-65yrs) controls. Serum total oxidant load was estimated by Ferrous oxidation product in xylenol orange version 2 (FOX2), total antioxidant status by ferric reducing capacity of serum (FRAP) .FBS was estimated by commercial kits adapted to autoanalyser. Results: Significant difference was observed in serum NO level between patients and controls (78.6+ 8.6 vs. 37.59+ 4.19μmol/L: p<0.000). Significantly high FOX 2 levels (12.4+ 2.6μmol/L vs. 4.33+ 1.7 μmol/L) and lower FRAPS level was observed in patients as compared to controls (61.37+31.64 μmol/L vs. 226.46+ 15.23 μmol/L). Conclusions: Hyperglycemia leads to nitrosative stress (increase NO level) and oxidative stress by increasing total oxidant load (FOX2), decreasing antioxidant capacity (FRAP).